Assessing regional species pools for restoration programs in Spain - del Barrio, Jose M.; Aunon, Francisco; de Ron, David; Alia, Ricardo (NEW FORESTS, 2013)
The relationship between current and potential distribution in 34 main Spanish forest tree species (data from the Third Spanish Forest Inventory) was determined using a Maximum Entropy functional approximation with climatic data as predictive variables. A method for detecting regional species pools at two different scales: biogeoclimatic classes (CLATERES classification), and forest landscape types (WWF classification) has been proposed. Then, the Absence percentage for a species (i.e. the proportion of landscapes types or biogeoclimatic classes in which the species is included in the regional species pool but is actually not present) was determined. Results show higher figures of Potential Species Richness in the Pyrenees and the Cantabrian Range, while inland or coastal Mediterranean semiarid landscapes have lower figures. Using a classification based on biogeoclimatic variables (CLATERES) improves precision when estimating Absent Species Richness. Absence percentage is zero or close to zero for five species (Pinus uncinata, Quercus robur, Quercus ilex, Quercus humilis and Juniperus communis), while for other six species (Acer pseudoplatanus, Fraxinus angustifolia, Alnus glutinosa, Populus alba, Sorbus aucuparia and Pinus pinea) the figures are higher than 0.6, which means the species is absent in more than 60 % of the landscapes or biogeoclimatic classes that it could inhabit. The relationships between tree life traits and the absence of species from the ecosystems studied is slight but non-dominant species, species not subjected to forest management, or zonal species are less widely distributed that their climatic potentiality indicates.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Absent species; Biogeoclimatic classification of Spain; Regional restoration programs; Spanish forest landscapes types; Tree species richness

Spatial Patterns and Predictors of Forest Carbon Stocks in Western Mediterranean - Vayreda, Jordi; Gracia, Marc; Canadell, Josep G; Retana, Javier (Ecosystems, 2012)
Mediterranean semi-arid forest ecosystems are especially sensitive to external forcing. An understanding of the relationship between forest carbon (C) stock, and environmental conditions and forest structure enable prediction of the impacts of climate change on C stocks and help to deﬁne management strategies that maximize the value of forests for C mitigation. Based on the national forest inventory of Spain (1997–2008 with 70,912 plots), we estimated the forest C stock and spatial variability in Peninsular Spain and, we determined the extent to which the observed patterns of stand C stock can be explained by structural and species richness, climate and disturbances. Spain has an average stand C stock of 45.1 Mg C/ha. Total C stock in living biomass is 621 Tg C (7.8% of the C stock of European forests). The statistical models show that structural richness, which is driven by past land use and life forest history including age, development stage, management activities, and disturbance regime, is the main predictor of stand tree C stock with larger C stocks in structurally richer stands. Richness of broadleaf species has a positive effect on both conifer and broadleaf forests, whereas richness of conifer species shows no signiﬁcant or even a negative effect on C stock. Climate variables have mainly an indirect effect through structural richness but a smaller direct predictive ability when all predictors are considered. To achieve a greater standing C stock, our results suggest promoting high structural richness by managing for uneven-aged stands and favoring broadleaf over conifer species.
Keywords: conifer and broadleaf forests; fire disturbance; Forest management; national forest inventory; Peninsular Spain; structural richness; tree carbon stock; Tree species richness; understory carbon stock; Water availability